A retrospective study on immune-related pneumonitis in patients with non-small-cell lung cancer undergoing treatment with PD-1/PD-L1 inhibitors. Issue 1 (31st December 2023) - Yakymenko, Dorthe; Skougaard, Kristin
ABSTRACT: Background: Lung cancer patients undergoing treatment with immune checkpoint inhibitors (ICIs) are at risk of developing immune-related (ir-)pneumonitis. Since lung cancer patients have competing reasons for respiratory symptoms, this poses a diagnostic challenge. This study aimed to explore diagnosis and management of ir-pneumonitis in this patient group. Materials and Methods: Suspected ir-pneumonitis was frequent in this group of patients. The cohort was characterized by high heterogeneity and lack of unequivocal diagnostic conclusions. Treatment of ir-pneumonitis was longer than recommended and involvement of pulmonologist was very infrequent. The result of this study reflects the difficulties in a daily clinical setting to diagnose and manage patients with lung cancer presenting with pulmonary symptoms. Results: Suspected ir-pneumonitis was frequent in this group of patients. The cohort was characterized by high heterogeneity and lack of unequivocal diagnostic conclusions. Treatment of ir-pneumonitis was longer than recommended and involvement of pulmonologist was very infrequent. The result of this study reflects the difficulties in a daily clinical setting to diagnose and manage patients with lung cancer presenting with pulmonary symptoms.